2016
DOI: 10.21608/jpp.2016.46140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress and Weed Control on Weeds, Broomrape and Yield in Some Faba Bean Varieties

Abstract: Broomrape and weeds are determining factors for faba bean cultivation in Egypt. In split split plot design for this reason two field experiments in clouded fifty treatments were conducted in naturally infested fields with weeds and broomrape (Orobanche crenata Forsk.) at Shandaweel Research Station, Sohag governorate during 2012/13 and 2013/14 winter seasons to study the effect of two water stress treatments (The irrigations regimes was 60% and 100% FC), five faba bean varieties namely (Giza843, Misr3, Nubaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
2
5
0
Order By: Relevance
“…Concerning of the interactions of the three faba bean cultivars and the previous weed control treatments gave the highest significant reduction on the annual weeds presented associated to control broomrape as parasitic weed and reflected that to give the highest yield and its components, addition to give the highest economic net gross in both seasons. These results are in agreement with those obtained by (Fakkar et al 2016;Eid et al 2017;El-Gedwy et al 2020;El-Sherbeni et al, 2021) they reported that spraying with glyphosate followed by hand pulling significantly increased faba bean yield and its components as compared to untreated. Finally: Roundup Star herbicide was the core of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning of the interactions of the three faba bean cultivars and the previous weed control treatments gave the highest significant reduction on the annual weeds presented associated to control broomrape as parasitic weed and reflected that to give the highest yield and its components, addition to give the highest economic net gross in both seasons. These results are in agreement with those obtained by (Fakkar et al 2016;Eid et al 2017;El-Gedwy et al 2020;El-Sherbeni et al, 2021) they reported that spraying with glyphosate followed by hand pulling significantly increased faba bean yield and its components as compared to untreated. Finally: Roundup Star herbicide was the core of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Ibrahim et al (2014) found that Giza 843 cultivar decreased dry weight of weeds and increased seed yield. Fakkar et al (2016) indicated that excelled cultivars of Nubaria1and 3 and Giza 843 than other cultivars and increase yield and its components by reducing the grassy and broad-leaved weeds, increased height of the plants, as well as increase the number of branches/plants compared with other cultivars. Giza 843 and Misr 3 cultivars were brief and partially resistant to broomrape infection, contrast Nubaria1 and 3, which were highly susceptible.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the combined of the two seasons, over all tested cultivars, the data show that the faba bean plants irrigated with two times had the highest significant values of water productivity (1.95kg / m 3 ) compared to those irrigated with 4 times which produced the lowest one (1.46kg/ m 3 ). Similar results were obtained by other investigators who found that the values of total water applied to faba bean / fed was decreased, while water use efficiency was generally increased when the plants were exposed to drought stress conditions by decreasing the number of irrigations up to 3 irrigations (Eid et al, 2008) or 4 irrigations (Fakkar et al, 2016).…”
Section: Water Relationssupporting
confidence: 90%
“…Other investigators found that exposing faba bean plants to any water drought stress caused a significant damaging for plant growth (Oukaltouma et al, 2021;Abdelhaleim et al, 2022), seed yield/ plant and its components (El-Emshaty et al, 2021;Yousry et al, 2021) and seed yield/ fed (Abdel-Ghany et al, 2016;EL-Mansoury & Saleh, 2017) but led to an increase in protein % (Mekkei, 2014;Megawer et al, 2017) and water use efficiency (Abdel Samie et al, 2021;Noreldin & Abd-Alla, 2022). Moreover, Fakkar et al (2016), Tawfik et al (2018) and El-Gabry & Morsi (2019) found that the faba bean cultivars differed in their behaviour and seed and water productivity under various drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%